BRAIN-COMPUTER INTERFACE APPARATUS AND OPERATING METHOD OF REDUCING BURDEN OF INDIVIDUAL CALIBRATION PROCESS BY CLUSTERING SUBJECTS BASED ON BRAIN ACTIVATION - KIM DONG JOO; LEE SE HO; KIM YOUNG TAK (2021)
The present invention relates to a technical spirit of minimizing a signal correcting process between users by utilizing a clustering technology based on brain activation. More specifically, the present invention relates to a technology of minimizing the signal correcting process between the users, as the intention of a measuring recipient is determined by using an intention determining model trained with respect to a relevant specific clustering model, after clustering a brain-wave signal of the measuring recipient by using a specific clustering model. According to an embodiment of the present invention, the brain-computer interface apparatus includes: a feature extracting unit; a clustering model generator; and a brain-wave processing unit. The feature extracting unit extracts a plurality of clustering feature points by using a frequency for each band of a brain-wave signal measured from a plurality of learning recipients. The clustering model generator generates a plurality of clustering models based on the plurality of clustering features which are extracted. The brain-wave processing unit constructs an intention determining model by performing machine learning for the brain-wave signal for each of the plurality of clustering models, determines the brain-wave signal of the measuring recipient which is newly measured, as any one clustering model of the plurality of clustering models, and determines the intention of the measuring recipient by using the intention determining model which is constructed. 본 발명은 뇌 활성도에 기반한 클러스터링 기술을 활용하여 사용자 간 신호 보정 과정을 최소화하는 기술적 사상에 관한 것으로, 보다 구체적으로, 측정 대상자의 뇌파 신호를 특정 클러스터링 모델로 클러스터링한 후, 해당 특정 클러스터링 모델에 대하여 학습된 의도 판단 모델을 이용하여 측정 대상자의 의도를 결정함에 따라 사용자 간 신호 보정 과정을 최소화하는 기술에 관한 것으로, 본 발명의 일실시예에 따른 뇌 컴퓨터 인터페이스 장치는 복수의 학습 대상자로부터 측정된 뇌파 신호의 밴드 별 주파수 파워를 이용하여 복수의 클러스터링 특징점을 추출하는 특징점 추출부, 상기 추출된 복수의 클러스터링 특징점에 기반하여 복수의 클러스터링 모델을 생성하는 클러스터링 모델 생성부 및 상기 생성된 복수의 클러스터링 모델 별 뇌파 신호를 기계학습하여 의도 판단 모델을 구축하고, 새롭게 측정된 측정 대상자의 뇌파 신호를 상기 복수의 클러스터링 모델 중 어느 하나의 클러스터링 모델로 결정하고, 상기 구축된 의도 판단 모델을 이용하여 상기 측정 대상자의 의도를 결정하는 뇌파 처리부를 포함할 수 있다.